Keanekaragaman Moluska di Pantai Pasir Putih Lampung Selatan - Gres Maretta; Nurhaida Widiani Hasan; Nella Indry Septiana (Biotropika: Journal of Tropical Biology, 2019)
Pantai Pasir Putih is an area with a variety of coastal substrates that store much diversity of Molluscs species. The diversity of Molluscs in the waters of Lampung is still little known, therefore research conducted at Pasir Putih Beach, South Lampung aims to determine the density and diversity of Molluscs, as well as to determine water quality. The sampling method used is line transect combined with the square method. Molluscs were found in 48 individuals from nine families (Cerithiidae, Neritidae, Throchidae, Conidae, Muricidae, Nassaridae, Columbariidae, Columbellidae, Buccinidae, and Mactridae). Based on the calculation of Molluscs density (10.33 Ind/m2; 5 Ind/m2; 0.67 Ind/m2.) The Shannon-Wiener Molluscs index on the Pasir Putih Beach was included in the low category (H value: 0 - 0.152). The results of the analysis of environmental factors show that the waters of the Pasir Putih Beach have not been polluted and are still good enough for Molluscs life.